Discontinuation of Eculizumab treatment after hematological remission in patients with atypical and drug-induced hemolytic uremic syndrome - Yeter Hasan H.; Derici Ulver; Arinsoy Turgay; Altok Kadriye; Erten Yasemin; Guz Galip (Sciendo, 2022)
Introduction. The aim was to evaluate the effect of therapeutic plasma exchange (TPE) and eculizumab on hematological and renal survival in atypical hemolytic uremic syndrome (aHUS), and additionally, to examine the reliability of discontinuation of eculizumab treatment.